2020
DOI: 10.3390/jrfm13100228
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of BASEL Accords on the Management of Vietnamese Commercial Banks

Abstract: This paper is an attempt to empirically examine the impact of Basel Accord regulatory guidelines on the risk-based capital adequacy regulation and bank risk management of Vietnamese commercial banks. Our research aims to assess how Vietnamese commercial banks manage their capital ratio and bank risk under the latest Basel Accord capital adequacy ratio requirements. Building on previous studies, this research uses a simultaneous equation modeling (SiEM) with three-stage least squares regression (3SLS) to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Nguyen (2020) finds a positive relationship between CAR and ROA for small-sized banks and a significant effect with Basel II implementation, but this relationship does not hold for large-sized banks. The management of the banks should strengthen the net income to increase the ROA and ROE (Pham and Daly, 2020;Sultan et al, 2021). Aspal and Nazneen (2014) examine the determinants of CAR in India from the 2008 to 2012 period.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Nguyen (2020) finds a positive relationship between CAR and ROA for small-sized banks and a significant effect with Basel II implementation, but this relationship does not hold for large-sized banks. The management of the banks should strengthen the net income to increase the ROA and ROE (Pham and Daly, 2020;Sultan et al, 2021). Aspal and Nazneen (2014) examine the determinants of CAR in India from the 2008 to 2012 period.…”
Section: Empirical Evidencementioning
confidence: 99%
“…One of the conventional objective functions in the field of ALM is the objective function based on the maximization of bank profit, and in the proposed models based on this objective function, it is difficult to apply changes in the existing parameters to reach the optimal values of the balance sheet and income statement parameters. Also, in the conducted studies, no special effort has been made to reduce the size of the balance sheet [101][102][103][104][105][106][107][108][109][110][111][112]. But, this article has tried to eliminate this gap in the studies conducted in the past.…”
Section: Introductionmentioning
confidence: 99%
“…According to International Monetary Fund's (IMF) compilation guide for 2019, capital adequacy is a key indicator of the financial soundness of banks. Studies have shown that bank capital requirements can promote financial stability through behavior modification (Bhatta, 2015) and that regulatory capital requirements can improve banks' financial performance and reduce risk-taking (Pham & Daly 2020). A study by Ghulam et al, (2021) examined the nexus between Basel capital requirements, Asian emerging markets profitability, and risk in the banking sector and found that regulatory capital has a positive effect on profitability while risk has a negative effect.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the Basel II framework of capital adequacy regulations has not effectively curbed risk-taking behavior in the banking industry (Demirguc-Kunt, et al, 2006;Janson, 2009). However, other research suggests moral hazard risk due to capital requirements, although it may negatively impact profitability (Hellmann et al, 2000;Lee & Hsieh, 2013;Pham & Daly, 2020). The main macroeconomic benefit of higher capital requirements is increased resilience in the banking sector and a reduced likelihood of a banking crisis, but there may also be temporary costs related to slower GDP growth due to higher financing costs for banks and the economy as a whole.…”
Section: Introductionmentioning
confidence: 99%